Fiestas patronales y el turismo religioso en la virgen del Guayco en la Provincia De Bolívar - Echeverría Meléndez, Katerine Jasmin (2019)
The present investigation is analyzed in the Virgen del Guayco located in the Parish L Magdalena, belonging to the Chimbo Canton of the Province of Bolívar, where the low tourist diffusion of the population and the entities on the historical and religious value of the Virgin is evidenced of the Guayco in the development of Religious Tourism, it is important to keep in mind that this is because there is no Tourism Planning that prevents achieving better management and management in activities, delaying the integration of tourism into society. The project presents the advantages of tourism activities as a great opportunity for cultural, economic and social progress, directly benefiting the population and improving their quality of life, exposing the new alternatives in tourism development. In the development of the research work a scientific methodology was used followed by methods and techniques that allowed the collection of information necessary for the development of the topic, using the respective surveys and interviews with the authorities of the Municipal GAD of the Chimbo Canton and the Parish Priest of the La Magdalena Parish about the importance of Religious Tourism in the sector. It was found that the population is currently awaiting other activities such as agriculture and, putting religious tourism in the background